PEMAKNAAN KHALAYAK TERHADAP FILM “MARLINA SI PEMBUNUH DALAM EMPAT BABAK” - Andrew Manogu N; Sri Budi Lestari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research is motivated by the presence of feminist films in the midst of the development of mainstream films (men as the main actors). So far women have decided as a complement to the story because of gender injustice caused by gender differences. The film